Enhanced electrochemical energy storage properties of carbon coated Co3O4 nanoparticles-reduced graphene oxide ternary nano-hybrids. Issue 11 (1st August 2020) - Aadil, Muhammad; Zulfiqar, Sonia; Sabeeh, Humera; Warsi, Muhammad Farooq; Shahid, Muhammad; Alsafari, Ibrahim A.; Shakir, Imran
Abstract: In this article, we have synthesized carbon-coated cobalt oxide nanoparticles (NPs) and their nanocomposite with reduced graphene oxide (C@Co3 O4 /r-GO) via chemical and ultrasonication techniques. The observed higher electrical conductivity (1.4 × 10 −3 S/m) of the nanocomposite than the pristine NPs (1.9 × 10 −8 S/m) was due to the combined effect of the carbon-coating and r-GO nanosheets. The higher specific surface area (118 m 2 /g) of the nanocomposite was due to the relived agglomeration of the NPs via the carbon-coating and r-GO matrix. The nanocomposite based electrode shows exceptional gravimetric capacitance of 674 F/g at 1 A/g and loses just 18% of its initial capacitance after 10 3 charges/discharge cycles. The superior electrochemical performance of the nanocomposite was due to its higher surface area and synergistic improvements between carbon-coated NPs and highly conductive r-GO nanosheets. In the nanocomposite, the r-GO nanosheets play a double role to increase the energy storage properties. For example, the r-GO sheets acted as a capacitive supplement as well as a conductive matrix for a speedy redox reaction. Highly conductive nanocomposite also showed lower charge transfer resistance (Rct 12.78 Ω) during the electrochemical impedance spectroscopic (EIS) tests that further facilitated the redox reaction to achieve higher pseudocapacitance. The observed electrical and electrochemical results demonstrate the potential of the C@Co3 O4 /r-GO nanocomposite for hybrid supercapacitors.